METHODOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF MODERN ECONOMIC SYSTEMS BASED ON DETERMINING THE IMPACT OF INNOVATIVE FACTORS - A. A. Sazonov (Вестник университета)
The technique for the development of modern economic systems, taking into account the influence of various groups of innovative factors has been created. The structural elements of the innovative economy, the features of the stability of modern economic systems have been revealed and also the main types of stability and ways to improve it have been determined. The object of study are multicomponent economic systems – industrial enterprises that are directly affected by various innovative factors of development. The method that allows you effectively implement various processes of planning and innovative development at high-tech enterprises in modern economic conditions have been proposed. The main indicators of the forecast of social, economic and innovative development of Russia from 2018 to 2020 have been presented. The problems that exist in the organization of public-private partnership have been considered.